Non-steroidal anti-inflammatory drugs are associated with emergency admission to hospital for colitis due to inflammatory bowel disease. Issue 5 (May 1997) - Evans, J M; McMahon, A D; Murray, F E; McDevitt, D G; MacDonald, T M
Abstract : BACKGROUND: To evaluate the relation between non-steroidal anti-inflammatory drugs (NSAIDs) and colitis due to inflammatory bowel disease. METHODS: A case-control study was conducted using a prospectively constructed, record linkage database containing hospital event and dispensed drug data (1989-93). The study population consisted of 319, 465 people resident in Tayside in January 1989, and still resident (or dead) in October 1994. RESULTS: Of the 785 patients admitted to hospital as emergencies with colitis between July 1989 and June 1993, 200 fulfilled the case criterion of colitis due to inflammatory bowel disease. A further 1198 persons were used as community controls. Odds ratios were calculated for three exposure periods (current, recent, and past exposure). The overall odds ratios (with 95% confidence intervals) for current and recent exposure to NSAIDs were 1.77 (1.01 to 3.10) and 1.93 (1.20 to 3.09) respectively. Current and recent exposure to NSAIDs was also associated for incident cases, with odds ratios of 2.96 (1.32 to 6.64) and 2.51 (1.13 to 5.55). There was a trend for recent exposure among non-incident cases. CONCLUSION: The use of NSAIDs may be associated with an increased risk of emergency admission to hospital for colitis due to inflammatory bowel disease, particularly among patients with no previous history.